Salvage Robot-Assisted Partial Nephrectomy for the Management of Renal Cell Carcinoma Following Failed Stereotactic Radiotherapy - Gorin, Michael A. (Society of Laparoendoscopic Surgeons, 2012)
Nephron-sparing surgery is currently the standard of care for the management of small renal masses. While both neoadjuvant and adjuvant conventional external beam radiotherapy have failed to demonstrate an oncologic benefit for the treatment of renal cell carcinoma, more recent work aims to explore the utility of stereotactic radiotherapy. We present the case of a 70-year-old woman who failed primary treatment of a small renal mass with the CyberKnife radiotherapy system and describe her successful salvage treatment with robot-assisted partial nephrectomy. This case demonstrates the safety of robotic surgery for the management of renal tumors following failed stereotactic radiotherapy.